2021
DOI: 10.3390/ani11010213
|View full text |Cite
|
Sign up to set email alerts
|

Training with Multiple Structurally Related Odorants Fails to Improve Generalization of Ammonium Nitrate Detection in Domesticated Dogs (Canis familiaris)

Abstract: A critical aspect of canine scent detection involves the animal’s ability to respond to odors based on prior odor training. In the current study, dogs (n = 12) were initially trained on an olfactory simple discrimination task using vanillin as the target odorant. Based on their performance on this task, dogs were assigned to experimental groups. Dogs in group 1 and 2 (n = 5 dogs/group; 1 dog/group were removed due to low motivation or high error rates) were trained with either two or six forms of ammonium nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Although training with high quantities of the target odor could be implemented with little risk for some detection dogs (e.g., narcotics detection dog), the implementation of this training method might be particularly challenging or dangerous for explosive detection dogs. Most of the research in canine generalization has evaluated training methods to improve generalization to different variants or mixtures of the target odor [ 5 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 28 ]. However, to our knowledge, no other study has evaluated generalization to different quantities of an explosive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although training with high quantities of the target odor could be implemented with little risk for some detection dogs (e.g., narcotics detection dog), the implementation of this training method might be particularly challenging or dangerous for explosive detection dogs. Most of the research in canine generalization has evaluated training methods to improve generalization to different variants or mixtures of the target odor [ 5 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 28 ]. However, to our knowledge, no other study has evaluated generalization to different quantities of an explosive.…”
Section: Discussionmentioning
confidence: 99%
“…The success of dogs as detectors relies on their sensitivity and ability to generalize and discriminate between similar and dissimilar odors. Olfactory generalization refers to the phenomenon where a dog produces the same response to perceptually similar odors that could share the same outcome [ 11 , 12 ]. In the field, olfactory generalization occurs when a dog alerts or shows the same trained behavioral response to variations of a target odor [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La revisión de la literatura que se ha hecho al respecto incluye artículos sobre el análisis forense (Furton et al, 2015) y otros que están a la vanguardia del desarrollo de nuevas medidas de seguridad para estudiar explosivos y artefactos explosivos improvisados (Prada-Tiedemann & Rodríguez, 2016;Lazarowski et al, 2020;Dorman et al, 2021), evaluando la asociación con los perros detectores de drogas y estupefacientes, lo que puede ser útil en futuras aplicaciones en contextos reales operacionales para la fuerza pública colombiana (Ejército, Armada Nacional, Fuerza Aérea y Policía), además de los demás operadores de justicia (fiscalía y jueces).…”
Section: Marco Teóricounclassified
“…That also shows the influence of the method of training on the results of odor detection, with the authors concluding that dogs could not spontaneously recognize a target component in an odor mixture after target-only training. Among the elements influencing the final results of olfactory work of the sniffing dogs is the issue of an animal’s ability to respond to odors based on prior odor training [ 206 ]. In this context, Dorman et al [ 206 ] showed that dogs trained with different forms of ammonium nitrate were unable to recognize the substance with an acceptable level of success when it was mixed with powdered aluminum, with the results from some animals no different to those expected by chance alone.…”
Section: Limitations In Canine Detection—a Critical Assessmentmentioning
confidence: 99%